2019
DOI: 10.1186/s43055-019-0104-x
|View full text |Cite
|
Sign up to set email alerts
|

Bi-caudate ratio as a MRI marker of white matter atrophy in multiple sclerosis and ischemic leukocencephalopathy

Abstract: Background: Brain atrophy measurement is now a cornerstone in basic neuro-imaging science. While assessment of white matter atrophy by visual inspection is subjective, volumetric approaches are time-consuming and not often feasible. Bi-caudate ratio represents a linear surrogate parameter of brain volume that can be derived from standard imaging sequences. This study highlights the value of the bi-caudate ratio (BCR) as a MRI marker of white matter atrophy in patients with multiple sclerosis and ischemic leuko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
(13 reference statements)
1
4
0
1
Order By: Relevance
“…However, there are no data concerning the impact of age on BCR in SDCNS patients. Thus, based on the accepted interpretation that BCR reflects deep frontal subcortical white matter atrophy [28,[33][34][35]49], our findings highlight a relationship between age and this process not only in MS but also in SDCNS patients. Another 2DLM commonly used to assess brain atrophy is 3VW.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, there are no data concerning the impact of age on BCR in SDCNS patients. Thus, based on the accepted interpretation that BCR reflects deep frontal subcortical white matter atrophy [28,[33][34][35]49], our findings highlight a relationship between age and this process not only in MS but also in SDCNS patients. Another 2DLM commonly used to assess brain atrophy is 3VW.…”
Section: Discussionsupporting
confidence: 68%
“…Additionally, 3V enlargement was also associated with higher T1LV and T2LV only in the MS group. Again, these observations might suggest that deep frontal subcortical white matter atrophy (measured by BCR) as well as central brain atrophy (represented by 3V enlargement) [28,[33][34][35]49,50] are significantly dependent on inflammatory and/or degenerative processes represented by focal white matter pathology in MS but not in SDCNS patients.…”
Section: Discussionmentioning
confidence: 98%
“…We found that there was a significant ( P < 0.01) reduction in the diameter of both these parameters, suggesting that curative surgery in patients with CS leads to a reversal of structural changes of the brain. [ 40 41 ] However, studies with long term follow-up are required to know that these changes are completely reversed and neuropsychiatric manifestations revert to normal after structural changes normalized.…”
Section: Discussionmentioning
confidence: 99%
“…Another promising but non-specific biomarker is chitinase-3-like-1 precursor (CHI3L1); CHI3L1 serum and CSF levels were found to be increased as the disease progressed. CHI3L1 is also associated with conversion from CIS to RRMS and is correlated with a higher relapse rate ( 16 ). Although some studies reported that the levels of osteopontin (OPN) were higher in the blood and CSF of MS patients and correlated with relapse rate and disease severity ( 17 , 18 ), others did not confirm these findings.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the need for simple but reliable measures of brain atrophy, linear atrophy parameters such as the bicaudate ratio (BCR) and the third ventricle width (TVW) were proposed ( 15 ). BCR is a surrogate marker of global supra-tentorial white matter atrophy ( 16 ), and the TVW corresponds with thalamic atrophy ( 17 ). Recently, it was shown that these two-dimensional parameters, which are easy and quick to measure in everyday practice, may be useful in the prognosis of disease progression ( 18 ).…”
Section: Introductionmentioning
confidence: 99%